CHEMICAL COMPOSITION AND IN VITRO RUMEN BIOGAS PRODUCTION OF SOME PERENNIAL PLANTS SPECIES - S. Medjekal; M. Guetouache; M. Ghadbane; A. Z. M. Salem (Journal of Animal and Plant Sciences, 2023)
The nutritive value of some Algerian perennial plants species were examined on the premise of their in vitro gas production, chemical composition and fermentation kinetics. The plant species were Aristida pungens, Artemesia herba-alba, Artemesia vulgarus, Atriplex halimus, Genista saharae, Lygeum spartum, Retama retam, Stipa tenacissima. L and oat hay as a standard. Importants variation have been registered (P <0.05) regarding all the chemical components of the perennial plants species. The crude protein (CP) content value ranged between 5.02 and 16.15 (% DM), the highest CP value was recorded for Atriplex halimus (A. halimus). Acid detergent fiber (ADF) and Neutral detergent fiber (NDF) were generally high in Stipa tenacissima and low in Atriplex halimus (P <0.05). The organic matter digestibility (OMD) and the total gas production vary from 31.74 to 59.1 % and 15.46 to 39.52 (ml.g-1 DM), respectively. In general, high values of Organic matter digestibility (OMD) and gas production were noted for A. halimus succeeded by Genista saharae (G. saharae). This necessitates prudent nutritional interventions such as supplementation with barley and wheat bran. Additionally, in order to improve fibrous feeds digestibility, some exogenous fibrolytic enzymes are of growing interest as additives to ruminant nutrition. A. halimus is a valuable plant that provides wildlife habitat and food for livestock. It is a very effective fodder element in mixed diets and as a supplement for livestock, mainly during the dry season in arid and semi-arid regions.
Keywords: digestibility; in vitro gas production; perennial plants